Fatigue life prediction of polymer matrix composites containing initial delamination using thermography - Amir Mohammad Feizi; Fathollah Taheri-Behrooz (Polymer Testing)
This study investigates the effect of initial delamination on the fatigue behavior and lifespan of composite laminates made of woven glass fabric and epoxy resin. The primary objective is to evaluate the influence of initial delamination on parameters such as fatigue limit, stiffness degradation, and temperature variations using infrared thermography. To investigate the effect of delamination, the specimens were fabricated in three categories: standard, symmetric delamination, and asymmetric delamination. Analysis of thermal data and mechanical results revealed that initial delamination reduced approximately 76.8 % in fatigue life and 15.8 % in fatigue limit. Additionally, specimens with initial delamination exhibited faster stiffness degradation and higher temperature rise, indicating accelerated crack propagation and greater stress concentration. A fatigue life prediction model based on entropy generation and thermal data was developed for both standard and delaminated specimens, demonstrating satisfactory accuracy. The findings of this research can enhance the design and performance of composite structures by improving safety and operational efficiency through non-destructive monitoring and fatigue life prediction.